Big Data promises value: is hardware technology taken onboard?. Issue 9 (19th October 2015) - Bhat, Wasim Ahmad; Quadri, S.M.K.
Abstract : Purpose: – The purpose of this paper is to explore the challenges posed by Big Data to current trends in computation, networking and storage technology at various stages of Big Data analysis. The work aims to bridge the gap between theory and practice, and highlight the areas of potential research. Design/methodology/approach: – The study employs a systematic and critical review of the relevant literature to explore the challenges posed by Big Data to hardware technology, and assess the worthiness of hardware technology at various stages of Big Data analysis. Online computer-databases were searched to identify the literature relevant to: Big Data requirements and challenges; and evolution and current trends of hardware technology. Findings: – The findings reveal that even though current hardware technology has not evolved with the motivation to support Big Data analysis, it significantly supports Big Data analysis at all stages. However, they also point toward some important shortcomings and challenges of current technology trends. These include: lack of intelligent Big Data sources; need for scalable real-time analysis capability; lack of support (in networks) for latency-bound applications; need for necessary augmentation (in network support) for peer-to-peer networks; and rethinking on cost-effective high-performance storage subsystem. Research limitations/implications: – The study suggests that a lot of research is yet to be done in hardware technology, if full potential of Big Data is to be unlocked. Practical implications: – The study suggests that practitioners need to meticulously choose the hardware infrastructure for Big Data considering the limitations of technology. Originality/value: – This research arms industry, enterprises and organizations with the concise and comprehensive technical-knowledge about the capability of current hardware technology trends in solving Big Data problems. It also highlights the areas of potential research and immediate attention which researchers can exploit to explore new ideas and existing practices.